Absence of Flexor Carpi Radialis during an Elective Carpometacarpal Arthroplasty of the Thumb: A Rare Anatomical Variation - Stratos S. Sofos; Muhammad Riaz (Case Reports in Medicine)
Purpose. We present an extremely rare anatomical variation of unilateral flexor carpi radialis (FCR) absence. This rare anatomical variation posed a clinical dilemma to us and we highlight the importance of the surgeon being aware of this anatomical variation of an important structure both as a reconstruction tool and as an anatomical landmark. Methods. This anatomical variation of the unilaterally absent FCR was found upon dissection during a carpometacarpal arthroplasty of the thumb. Results. Upon the discovery of an absent FCR tendon, we proceeded with a simple trapeziectomy. Conclusions. We present an extremely rare anatomical variation of unilateral FCR absence. This rare anatomical variation may pose clinical dilemmas to the operating surgeon who aims to utilise the FCR either for tendon transfer, for tendon graft, or, as seen in our case, in the reconstruction of a carpometacarpal excision at the thumb. We highlight this diagnosis of suspicion, which may influence the clinical procedure.